Automatic Selection of Test Cases for Regression Testing - Magalhães, Cláudio; Barros, Flávia; Mota, Alexandre; Maia, Eliot (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2016: Anais do I Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2016)
Regression testing is a safety measure to attest that changes made on a system preserve prior accepted behavior. Identifying which test cases must compose a regression test suite in a certain development stage is tricky, particularly when one only has test cases and change requests described in natural language, and the execution of the test suite will be performed manually. That is the case of our industrial partner. We propose a selection of regression test cases based on information retrieval and implement as a web-service. In performed experiments, we show that we can improve the creation of regression test suites of our industrial partner by providing more effective test cases based on keywords analysis in an automatic way.